The Making of the Independent Short Film, Teatriños: Homenaxe ao mineral do repolo (Little Theatres: Homage to the Mineral of Cabbage) - Stephanie Dudley (Canada and Beyond, 2012)
This is a personal story of the process of making the short film, Little Theatres: Homage to the Mineral of Cabbage. The film is based on the poem by Erín Moure, Homage to the Mineral of Cabbage, from her book, Little Theatres.